2014
DOI: 10.1371/journal.pone.0094478
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Complement-C1q TNF-Related Protein 1 Levels Are Increased in Patients with Type 2 Diabetes and Are Associated with Insulin Sensitivity in Chinese Subjects

Abstract: BackgroundComplement-C1q TNF-related protein 1 (CTRP1), a member of the CTRP superfamily, possesses anti-inflammatory and anti-diabetic effects in mice. However, the clinical relevance of CTRP1 has been seldom explored. The current study aimed to investigate the association of circulating CTRP1 and type 2 diabetes mellitus (T2DM) in a Chinese population.Design and MethodsSerum CTRP1 and adiponectin levels of 96 T2DM patients and 85 healthy subjects were determined by ELISA, and their associations with adiposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 30 publications
14
28
1
Order By: Relevance
“…It worth also mentioning that our data is inconsistent with some investigations that indicated the high plasma level of CTRP1 in NAFLD and T2DM [10]. This might be a possible explanation for the compensatory role of CTRP1 which increased in coronary artery disease and T2DM patients [1517]. …”
Section: Discussioncontrasting
confidence: 99%
“…It worth also mentioning that our data is inconsistent with some investigations that indicated the high plasma level of CTRP1 in NAFLD and T2DM [10]. This might be a possible explanation for the compensatory role of CTRP1 which increased in coronary artery disease and T2DM patients [1517]. …”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that CTRP1 displays insulin-sensitizing effects (8,14). Clinical evidence has shown that circulating CTRP1 levels are increased in association with metabolic syndrome, type 2 diabetes, and ischemic heart disease (10)(11)(12)(13). Given that most adipokines with protective cardiometabolic effects, including adiponectin, are downregulated by obesity (4,16,38), CTRP1 may serve as a unique adipokine that is up-regulated by the complications of obesity, presumably as a compensatory response to mitigate metabolic and cardiac disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It is up-regulated in adipose tissue in diabetic rats, and its expression is stimulated by proinflammatory cytokines (9). Clinical evidence has shown that high levels of circulating CTRP1 are associated with metabolic syndrome and type 2 diabetes (10)(11)(12). In a recent study, we demonstrated that plasma CTRP1 levels are increased in patients with coronary artery disease (13).…”
mentioning
confidence: 94%
“…Serum CTRP1 levels were significantly increased in patients with T2DM [19,20] and plasma Aldosterone concentration is elevated in patients with diabetes mellitus [15]. Study group with diabetic nephropathy was selected because DN is associated with hypertension.…”
Section: Discussionmentioning
confidence: 99%